Socio-economic models in geography (Methuen, 1967)
This book explores the theme of geographical generalization, or model building. It is composed of seven of the chapters from the original Models in Geography, published in 1967. The first chapter broadly outlines this theme and examines the nature and function of generalized statements, ranging from conceptual models to scale models, in a geographical context. The following six chapters deal with socio-economic building in geography.